Students’ Attitudes toward English Learning at a Muhammadiyah Junior High School: A Study at a Muhammadiyah Junior High School - Zahwa Rizky Aulia Zahwa; Washlurachim Safitri; Fetriani (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
English plays a crucial role in supporting students’ academic development and global communication skills, making it a compulsory subject in Indonesian junior high schools. However, students’ success in learning English is strongly influenced by affective factors, particularly attitude. This study aimed to examine seventh-grade students’ attitudes toward English learning at a Muhammadiyah Junior High School in Bengkulu City by exploring affective, cognitive, and behavioral dimensions. A descriptive quantitative research design was employed involving 19 students selected through total sampling. Data were collected using a Likert-scale questionnaire supported by classroom observations and analyzed using descriptive statistics. The findings revealed that students generally demonstrated positive attitudes toward English learning, indicated by a mean score of 3.21 and 81% favorable responses. Students showed emotional enjoyment, recognized the usefulness of English for future opportunities, and actively participated in classroom activities. However, several learners still experienced low confidence in speaking English due to anxiety and fear of making mistakes. These results suggest that while students possess supportive attitudes toward English, pedagogical strategies are needed to foster confidence and transform positive perceptions into effective language use. This study highlights the importance of creating supportive and interactive learning environments to enhance students’ engagement in English learning. Keywords: students’ attitudes, English learning, affective factors, junior high school, EFL context